Impact ofÂ agricultural waste onÂ theÂ shrinkâswell behavior andÂ cracking dynamics ofÂ expansive soils - Siviwe Odwa Malongweni; Yasutaka Kihara; Kuniaki Sato; Takeo Tokunari; Tabhorbayar Sobuda; Kaya Mrubata; Tsugiyuki Masunaga (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The swelling characteristics and cracking of expansive clayey soils usually lead to their low yield, and as a result, large areas of expansive soils remain uncultivated and unproductive. There is a need for the development of simple, low-cost technologies which will bring these soils into production. The amendment of expansive clayey soils with agricultural waste products is a key goal for enhancing their production potential. Therefore, a study was conducted to evaluate the ameliorative effects of crop residues on the physiochemical and mechanical properties of expansive clayey soils. Method In this study, the potential soil amendments used include uncharred rice husk, rice husk biochar, uncharred sugarcane bagasse, and sugarcane bagasse biochar. The biochar was pyrolyzed at 450 °C. The amendments were applied into the soil at four applications rates: 0, 2, 5, and 10% by weight of soil (w/w), respectively. The mixture was then incubated in a glasshouse for 280 days. Results Charred and uncharred rice husk and sugarcane bagasse improved the physico-mechanical properties related to soil expansion. The liquid limit (LL), plastic limit (PL), plasticity (PI), coefficient of linier extensibility (COLEcore), volumetric shrinkage (VS), fissuresâ dimensions, and crack area density (CAD) of the soil decreased with an increase in treatment application rate. On the contrary, saturated water content increased with an increase in dosage. Conclusion 10% level of amendment application resulted in significantly improved soil properties than either 2% or 5% doses. Moreover, 2% level of amendment application is more preferable than 5% according to feasibility and economic point of view.